Optimal restoration schedules of transportation network considering resilience - Liu, Kezhi; Zhai, Changhai; Dong, You (Structure and infrastructure engineering, 2021)
Transportation network is of vital importance for city maintaining and reconstruction especially after extreme events. Decisions on the restoration plan of transportation network have to be made in a short period after event, but taking into account various decision-making criteria and resource constraints. This paper explains the essential problems in network restoration scheduling, and presents a novel resilience-based optimisation model for post-disaster urban transportation network restoration. The proposed method could obtain a set of general optimal restoration schedules in an efficient manner, so that decision-makers could make a final choice by weighting other preferences and experience. In the methodology, a new travel speed-based metric is introduced for performance assessment of transportation network, and three normalised independent indicators are developed to characterise network resilience from the perspective of functionality curve. Furthermore, a bi-objective optimisation model based on the recovery trajectory is recommended to search for non-dominated optimal restoration schedules. To illustrate the proposed method, heuristic algorithms are used to solve the restoration schedule optimisation problem of a hypothetical transportation network.